2022
DOI: 10.3390/ma15113877
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Synthesis of Aspergillus terreus Mediated Gold Nanoparticle: Antimicrobial, Antioxidant, Antifungal and In Vitro Cytotoxicity Studies

Abstract: Gold nanoparticles (GNP) were bio-fabricated utilizing the methanolic extract of the endophytic isolate Aspergillus terreus. The biosynthesised gold nanoparticles (GNP023) were characterised using UV-visible spectroscopy (UV-Vis); transmission electron microscopy (TEM), Fourier-transform nfrared spectroscopy (FTIR) and X-ray diffraction (XRD) studies. The bio-fabricated GNP023 displayed a sharp SPR peak at 536 nm, were spherically shaped, and had an average size between 10–16 nm. The EDX profile confirmed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 58 publications
3
2
0
Order By: Relevance
“…This result is similar to that of an earlier article [66]. The EDS profile of VPPE-AuNPs showed a strong signal for the presence of Au atoms and the sharp absorption peaks between 1-3 keV signify the existence of the Au particles (Figure 1C), which corroborates earlier reports [63,66]. Additionally, the occurrence of C, N, and O in the EDS spectra of VPPE-AuNPs could be due to the VPP extract used in the biosynthesis of VPPE-AuNPs.…”
Section: Vppe-aunp Manufacture and Analysissupporting
confidence: 92%
See 4 more Smart Citations
“…This result is similar to that of an earlier article [66]. The EDS profile of VPPE-AuNPs showed a strong signal for the presence of Au atoms and the sharp absorption peaks between 1-3 keV signify the existence of the Au particles (Figure 1C), which corroborates earlier reports [63,66]. Additionally, the occurrence of C, N, and O in the EDS spectra of VPPE-AuNPs could be due to the VPP extract used in the biosynthesis of VPPE-AuNPs.…”
Section: Vppe-aunp Manufacture and Analysissupporting
confidence: 92%
“…Next, the test reaction was also subjected to spectral analysis using a spectrophotometer at regular time intervals from 0 to 24 h (Figure 1A). The VPPE-AuNPs' reaction kinetics was examined by UV-Vis spectral analysis from 300-700 nm and it displayed a maximum absorption at 552 nm (surface plasmon resonance, SPR) (Figure 1A), which is similar to earlier published reports [62,63]. As specified in earlier studies [62,63], AuNPs characteristically demonstrated just a single SPR band from 500-560 nm, and similar results were also reported here.…”
Section: Vppe-aunp Manufacture and Analysissupporting
confidence: 89%
See 3 more Smart Citations